Prognostic uncertainty and accountability, moral uncertainty and ‘value lock-in’: Three epistemological challenges for long-term governance and their ethical implications - Tobias Hainz (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2025)
This article discusses long-term governance from an epistemological and ethical perspective. It focuses on three epistemological challenges for long-term governance and their profound ethical implications. The first challenge lies at the intersection of prognostic uncertainty about the distant future and the assignment of accountability to policymakers in the present. On what basis should policymakers be held accountable for their decisions if the long-term effects are hardly predictable given the knowledge available at the time of decision? The second challenge is moral uncertainty—not uncertainty about facts, but about which ethical theory to follow in decision-making and how to interpret it. Finally, the concept of ‘value lock-in’ and its epistemological challenges in relation to long-term governance are explained. The article concludes that such challenges deserve considerable further research attention because of their implications for effective long-term governance.